Selective Targeting of Tumor and Stromal Cells By a Nanocarrier System Displaying Lipidated Cathepsin B Inhibitor1. Issue 38 (27th June 2014) - Mikhaylov, G.; Klimpel, D.; Schaschke, N.; Mikac, U.; Vizovisek, M.; Fonovic, M.; Turk, V.; Turk, Boris; Vasiljeva, Olga
Abstract Cathepsin B (CtsB) is a lysosomal cysteine proteinase that is specifically translocated to the extracellular milieu during cancer progression. The development of a lipidated CtsB inhibitor incorporated into the envelope of a liposomal nanocarrier (LNC‐NS‐629) is described. Ex vivo and in vivo studies confirmed selective targeting and internalization of LNC‐NS‐629 by tumor and stromal cells, thus validating CtsB targeting as a highly promising approach to cancer diagnosis and treatment.